Changes in Steam Pipeline Properties after Long-term Exposure - Svobodova, Jaroslava; Benes, Libor; Brabec, Jaroslav (Manufacturing Technology Journal, 2020)
The article deals with a practical problem solution of the steel 15 128 steam pipeline properties change after prolonged exposure. Steam pipelines made of steel are stressed for a long time at higher temperatures and pressures and under conditions that are not constant throughout the pipeline operation. During operation, it occurs in the degradation processes, which are accompanied by changes in structure and mechanical properties. In terms of mechanical properties, it is mainly important the impact strength. The paper examines steam pipeline after long-term exploitation and results from microstructure evaluation, fractographic analysis, and comparison of impact strength test results.
Keywords: Steam pipeline properties; Mechanical properties; Microstructure; Impact resistance